An Amalgam of Voices: A Prismatic Approach to Memory and History in Gipi's Graphic Novels. Issue 2 (1st September 2022) - Takakjian, Cara
Abstract: The contemporary Italian comics artist and author Gipi offers us a narrative approach that speaks to, and for, the twenty-first century. He uses a multi-planed presentation of events that allows for memory and history to be pluri-temporal and pluri-vocal. Gipi's storytelling navigates a path through micro-histories and history, as he effectively reinserts individual memories and experiences into our continual recreation and reinterpretation of the past. His technique brings together an amalgam of voices and perspectives, real and imagined, that remain distinct yet melded together in his reconstruction and retelling of events. Ultimately, it responds to the question of how we can reimagine and recount history, and comments on the ethical implications of our involvement in the making of history.